(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The COVID-19 pandemic has profoundly impacted healthcare systems worldwide, posing significant challenges to healthcare workers’ ability to respond effectively (World Health Organization, 2020). Nurses, being frontline healthcare providers, play a crucial role in preventing, managing, and controlling the disease. Due to their direct contact with infected patients, their knowledge, attitudes, and practices (KAP) regarding COVID-19 are vital in reducing transmission and ensuring quality care delivery (Bhagavathula et al., 2020). Globally, healthcare workers have faced numerous challenges, including shortages of personal protective equipment (PPE), mental health strain, and evolving guidelines for COVID-19 management (Haque et al., 2021). Studies have shown that higher knowledge levels among healthcare providers lead to better adherence to infection control measures (Zhong et al., 2020). However, misconceptions and inadequate standardized training hinder optimal infection prevention strategies (Saqlain et al., 2020). In Pakistan, the healthcare infrastructure has been severely strained by the rapid surge in COVID-19 cases, highlighting the urgent need for capacity-building initiatives among healthcare professionals (Noreen et al., 2020). Nurses in tertiary care hospitals are expected to have a strong understanding of COVID-19 prevention measures and a positive attitude toward implementing safety protocols. However, gaps in knowledge and practice remain a concern, necessitating further research into their preparedness and response to the pandemic (Khan et al., 2021). This study investigates the knowledge, attitudes, and practices of staff nurses working in a tertiary care hospital in Karachi, Pakistan. By identifying potential gaps, the study aims to provide evidence-based recommendations to enhance training, improve adherence to infection control protocols, and support healthcare systems in managing future outbreaks. Aim This study aims to assess the knowledge, attitude, and practices of staff nurses regarding COVID-19 in a tertiary healthcare hospital in Karachi, Pakistan. The findings will help identify existing gaps and provide recommendations for improving infection control strategies within the nursing community. Objectives To assess the knowledge, Attitude & Practices of staff nurses regarding COVID-19. Methodology In this cross-sectional study, 180 nurses with valid PNC cards at a tertiary care hospital in Karachi were selected through convenient sampling. Data was collected through questionnaires. The survey included queries related to demographic variables and knowledge, Attitude & Practices of staff nurses regarding COVID-19. The data was then analyzed, with results presented in terms of percentages, frequencies for qualitative variables, and mean values with standard deviations for quantitative variables. The Chi-square test was used to explore the relationship between demographic factors and nurses’ attitudes towards Covid -19. Results Demographics: The majority of participants (42%) were aged 31-35 years, with a higher proportion of male nurses (58%). Most had over five years of experience (56%). 93% of staff nurses correctly identified clinical signs and symptoms of COVID-19.63.9% of nurses exhibited a positive attitude towards COVID-19 management, influenced by mass media exposure.84% of nurses adhered to safe practices such as hand hygiene and personal protective equipment (PPE) usage. The chi-square test showed a significant association (p<0.001) between higher knowledge levels and adherence to COVID-19 protocols. Regression analysis indicated that work experience (β = 0.43, p<0.05) and formal training (β = 0.37, p<0.05) were significant predictors of positive attitudes toward COVID-19. Conclusion This study found that staff nurses in Karachi have a high level of knowledge and adherence to safe practices regarding COVID-19. However, attitudes can be further improved through targeted training programs. The statistical analysis underscores the importance of work experience and training in shaping positive attitudes and adherence to infection control measures.